Workplace Flexibility A Bibliometric Analysis - Rifqi Hisyam Mahendra; Madziatul Churiyah (CV. Syntax Corporation Indonesia, 2022)
This research aims to further understand the effect of employee involvement and fairness in an organization that is perceived to have a positive workplace atmosphere. The mediating role of employee involvement in linking workplace flexibility with the behavior of co-workers, of course, the perception of fairness for every worker must absolutely be obtained in the work environment. Therefore, the aim of this research is to provide a reference for an extensive bibliometric study of the relationship between employees and the work environment. After managing the article data base compiled from Scopus from 55 articles found that were run from 2018-2020 there were 20 articles analyzed in this study. and analyzed managing with VOSviewer software to analyze co-authorship, co-accurance, and citation. Overall, this literature study provides an appropriate reference point for further research on the topic of Workplace Flexibility